Correlates of physical activity level among hemodialysis patients in Selangor, Malaysia. - Wong, S.W.; Chan, Yoke Mun; Lim , Christopher Thiam Seong (2011)
INTRODUCTION: There is mounting evidence demonstrating the importance of adequate physical activity to promote better well-being among hemodialysis patients. Available data pertaining to the levels of physical activity and its determinants among hemodialysis patients is, however, scarce in Malaysia. The objectives of this study are hence to determine the levels of physical activity and it associated factors among hemodialysis patients. METHODOLOGY: A total of 70 subjects were recruited from three dialysis centres in Selangor. A face-to-face interview was conducted to obtain socio-demographic data and subjects' knowledge on dietary sources. Medical history, biochemical parameters and weight status were obtained from medical records. Physical activity level (PAL) was assessed using the Global Physical Activity Questionnaire (GPAQ). RESULTS: A total of 81.4% and 18.6% of the respondents had low and moderate PALs, respectively. Thus, none of the respondents had high PAL. Serum creatinine, education level, personal income and knowledge score on potassium-related medical complications were factors found to correlate significantly with PAL. Multiple linear regression analysis showed that higher PAL was predicted by a lower knowledge score on dietary sodium source, higher education and higher serum creatinine. CONCLUSION: Despite consistent documentation of the potential positive impact of physical exercise on hemodialysis outcomes, the level of physical activity remains low among these patients. It is hoped that these findings can add to the existing body of knowledge and serve as a supporting document for the formulation of appropriate interventions to improve the status of physical activity among hemodialysis patients in Malaysia.